MULTIPLE STATE MODEL FOR PREMIUM CALCULATION OF THE ELDERLY LONG-TERM CARE INSURANCE - Aini, Nadhira Fajri; Ruhiyat, Ruhiyat; Erliana, Windiani (PATTIMURA UNIVERSITY, 2025)
As Indonesia enters an ageing population phase—with 12% of its population categorized as elderly—the need for financial protection in later life is increasingly urgent. The elderly population faces declining economic productivity, increased health risks, and a growing need for long-term care support. To address this, the present study develops an actuarial framework for calculating net annual premiums for elderly long-term care (LTC) insurance using the equivalence principle and a five-state multiple state model. Unlike previous research that focused on critical illness insurance, the proposed model reflects elderly care needs more realistically by incorporates transitions into and out of dependency where the elderly need assistance to perform daily activities. The results show that premiums rise significantly with later enrollment ages due to higher dependency and mortality risks along with shorter contribution periods. Furthermore, cash flow simulations based on 500 life table iterations demonstrate that LTC insurance can remain financially sustainable when accurately priced and supported by stable investment returns. This study offers a novel actuarial approach to developing sustainable LTC insurance products for Indonesia’s ageing population.